The Sensitivity Test of Mycobacterium tuberculosis to Snail Seromucoid and Chitosan in vitro - Yusup Subagio Sutanto; Magdalena Sutanto; Agnes Sri Harti; Nony Puspawati (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2021)
Tuberculosis (TB) is an infection caused by M. tuberculosis (MTb) and is transmitted through droplets of phlegm in the air from patients or those suspected of having TB. In general, treatment for TB is done with anti-tuberculosis drugs (ATDs), specifically streptomycin, isoniazid, rifampicin, and ethambutol (SIRE) that takes a long time due to the level of resistance of MTb bacteria. The resistance of MTb triggers ATDs based on natural bioactive compounds. Chitosan as a result of chitin deacetylation can function as an antimicrobial agent because it is polycationic, which is biodegradable, biocompatible, and non-toxic. Snail (Achatina fulica) seromucoid contains antibacterial bioactive compounds, namely glycans, peptides, glycopeptides, achasin protein, and chondroitin sulfate. This study aims at testing the sensitivity of MTb isolates against snail seromucoid and chitosan in vitro. This research applied the experimental research method. MTb isolates were obtained from sputum samples of patients suspected of TB at the Surakarta Regional Public Hospital (RSUD Surakarta). The results of screening for MTb were positive, based on the microscopic examination of MTb using the Ziehl Nelson (ZN) method, the MPT 64 rapid test, and the quick molecular test using the Genexpert method. The research was completed through several stages, including the preparation of a suspension of germs with a concentration of 1 mg/ml or Mc. Farland 0.5-1.0; preparation of the stock solution and working solution (WS); drug sensitivity test (DST) against snail seromucoid; chitosan and ATDs (SIRE) on Lowenstein Jensen (LJ) media; and incubation at 37°C for 3-4 weeks. The results were interpreted on day 28 or day 42. The results have revealed that MTb isolates are 100% resistant to snail seromucoid and 2% chitosan. This study concludes that MTb isolates from suspected TB are resilient to 100% snail seromucoid and 2% chitosan.